Propiedades mecánicas de metales nanoporosos . - Ruestes, Carlos J. (Comisión Nacional de Energía Atómica. Instituto Balseiro, 2015)
Fil. Ruestes, Carlos J.. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina